Enantioselective Electrochemical Lactonization Using Chiral Iodoarenes as Mediators - Gao, Wen-Chao; Xiong, Zi-Yue; Pirhaghani, Shafigh; Wirth, Thomas (Synthesis, 2019)
The enantioselective electrochemical lactonization of diketo acid derivatives using chiral iodoarenes as redox mediators is reported for the first time. Good to high stereoselectivities are observed in the lactonization and also in intermolecular α-alkoxylations of diketo ester derivatives. This enantioselective process was then adapted to an electrochemical flow microreactor where only small amounts of supporting electrolyte were necessary.
Keywords: electrolysis; flow microreactors; hypervalent iodine; lactonization; stereoselective synthesis